Association between eosinophil count and prognosis in chronic obstructive pulmonary disease patients - Hsu, Wan-Hsuan; Shiau, Bo-Wen; Lai, Chih-Cheng; Liao, Kuang-Ming (Frontiers in Medicine, 2025)
BackgroundThe association between blood eosinophil levels and the risk of increased exacerbations, acute respiratory failure (ARF) and mortality in chronic obstructive pulmonary diseases (COPD) remains controversial. This association may predict future exacerbations and clinical outcomes among patients with COPD. This study aimed to clarify the relationship between eosinophil count and risk of acute exacerbation, ARF and mortality s in patients with COPD.MethodsThe data for this retrospective cohort study were collected from TriNetX, a global multicentre research database. Using the Global Collaborative Research Networks, patients aged > 40 years with a diagnosis of COPD were examined for the association between blood eosinophil counts and the risk of acute exacerbation during a 3-year follow-up period. Cox proportional hazard models and Kaplan–Meier analysis were used to assess the risk of acute exacerbation between the non-eosinophilic (blood eosinophil counts <300 cells/μL) and eosinophilic groups (≥300 cells/μL) after propensity score matching. Other outcomes including survival and ARF, were also examined.ResultsThe non-eosinophilic group had a 1.27-fold lower risk of acute exacerbations of COPD (hazard ratio [HR], 0.790; 95% confidence interval [95% CI], 0.74–0.85; p < 0.001), a 1.22-fold lower risk of all-cause mortality (HR, 0.818; 95% CI, 0.76–0.88; p < 0.001) and a 1.39-fold lower risk of ARF (HR, 0.721; 95% CI, 0.66–0.78; p < 0.001) compared to the eosinophilic group during the 3-year follow-up period.ConclusionIncreased eosinophil count may be linked to an elevated risk of exacerbation, respiratory failure, and mortality in COPD.